“Era um veí um cidade”, o sintagma nominal na escrita de jovens e adultos: tensão e conflito na composição da sintaxe de concordância nominal - Santos, Eudes da Silva (2011)
The "Noun Phrase" - NP - is a linguistic category that has been much discussed by scholars of various strands. We analysed, in this study, specifically, the "noun phrase" with violations in "Nominal Concordance" -NC- between the constituents that made them. Anchored in the work of Calil (2004; 2007 and 2008) and Felipeto (2007), among others, to discuss about the manifestations, "errors", singular or not, from the writing in school. We described and analysed the "error" which occurs, mainly,in the (lack of) concordance that occurs within a NP, for example , "uma vez", composing the famous expression "era uma vez", mark of the openings from fairy tales, also, in the "noun phrase" that fallows this expression, which possibly have been interfered with it in their composition, for example , in " era um vez um menina" and "era um veí um cidade" . The strangeness that these compositions have caused us, beyond the violations of concordance between the constituents of this kind of "noun phrase", alternated with the writing of the NPs stabilized in the language, extends to the use of "era uma vez" in ghost tales, whose openings are not like fairy tales. Under the gaze of the acquisition of written language, we take this element, the "error" of "nominal concordance" in NPs, as something that constitutes the process of teaching and learning of young and adult‘s students. The collection of data aimed to work at the textual production, through the ghost tales, which was made from the creation of stories by students, using as a teaching strategy, especially the production in doubles. We analyzed, for this study. Twenty manifestations of "noun phrase‖ with the violation of concordance, a corpus of 198 (one hundred and ninety eight) manuscripts from students of EJA, during the year of 2005 in a class of 2nd phase from a municipal school in an elementary school of Maceio – AL. For this, we assume the proposals of Lemos (1992; 1997; 2002 and 2006), among others, through play that occurs between the processes that is entitled as a metaphoric and metonymic, but also that what Calil & Felipeto (2008) say about the "error' in the analysis of manuscripts of students in the acquisition process of writing, either within the phonology, syntax, morphology, among others. Corroborating with the studies mentioned above, our results indicated that the "error" of concordance is constitutive in the process of acquiring these scripters, we indentified, as commanded by the operation of linguistic-discursive of the language, individual marks, each subjected by its writer. This probably contributed in/for the formation of the "noun phrase" that violated the concordance.